The Ideal Education Concept According to Ibn Khaldun's Thought: Relevance and Application in the Modern Era - Nur Hasanah, Muwahidah; Asroriah, Fatimatul; Chasanah, Umi (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
This study aims to explore the concept of ideal education according to Ibn Khaldun's thought as outlined in his book Muqaddimah, and to analyze its relevance and potential implementation in the context of modern education, particularly in Indonesia. Through a qualitative literature review method, this study identifies and examines the main aspects of Ibn Khaldun's educational thought, including educational objectives, teaching methods, curriculum, the role of teachers, and the learning environment. The findings indicate that Ibn Khaldun has a holistic and comprehensive view of education that emphasizes the balance between intellectual, moral, and spiritual development. The relevance of his ideas to modern education is reflected in various contemporary approaches, such as interactive learning and integrative curricula. The study also reveals that many of Ibn Khaldun's educational principles can be adapted to the Indonesian education system to enhance the quality and effectiveness of learning. The conclusion of this research underscores the importance of integrating historical values relevant to modern educational needs to create a more holistic and inclusive education system. Recommendations are provided for further research focusing on the practical implementation of Ibn Khaldun's educational concepts in various educational contexts.